Corporate Ethical Identity as a Determinant of Firm Performance: A Test of the Mediating Role of Stakeholder Satisfaction - Berrone, Pascual (Journal of business ethics, 2007)
In this article, we empirically assess the impact of corporate ethical identity (CEI) on a firm’s financial performance. Drawing on formulations of normative and instrumental stakeholder theory, we argue that firms with a strong ethical identity achieve a greater degree of stakeholder satisfaction (SS), which, in turn, positively influences a firm’s financial performance. We analyze two dimensions of the CEI of firms: corporate revealed ethics and corporate applied ethics. Our results indicate that revealed ethics has informational worth and enhances shareholder value, whereas applied ethics has a positive impact through the improvement of SS. However, revealed ethics by itself (i.e. decoupled from ethical initiatives) is not sufficient to boost economic performance.